The Politics of Economic Inequality in Developing Countries - Nel, P. author. aut Link
VIII, 206 p.
Keywords: Inequalities of wealth and income have a significant impact for the achievement of economic, political and human development in developing counties. This book argues that a high level of economic inequality undermines a country's growth potential, retards the development of social capital, and encourages corruption.